PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN SIKAP ILMIAH DAN PRESTASI BELAJAR SISWA - Patra Awansyah (UNIB Press, 2022)
This study aims to describe the scientific attitudes and student achievement and to determine the effectiveness of the application of experimental methods on student achievement. The method used in this research is a combination method of classroom action research and quasi-experimental research. The subjects of the classroom action research were students of grade V SD Negeri 9 Tanjung Sakti Pumu for the academic year 2020/2021 even semester totaling 22 students. The population in this quasi-experimental research was all grade V students of the State Elementary School of Gugus II Tanjung Sakti Pumu. The research sample was selected by two classes in SD Negeri 9 Tanjung Sakti Pumu, namely class Va and Vb. Data collection techniques using observation sheets and tests. Data analysis using mean (mean) and t-test. The results of the study concluded that: The application of experimental methods can improve students' scientific attitudes; The application of the experimental method can significantly improve student achievement, and the application of the experimental method can effectively improve student achievement